Anyway, looking at the first sequent, the fourth premiss looks redundant to me.
On top of that it's not a valid sequent.
Consider the valuation: v(F) = T, v(N) = F, v(D) = T, v(P) = F.
However, replace the conclusion by its negation; then the sequent is valid and a derivation is pretty straight forward.
The big steps would be two applicatons of the rule of inference formulation of complex constructive dilemma.
At that point, you'll have (F V N) & (~F V ~N). (Think definition of exclusive disjunction.) The rest is busy work.